Hubungan Tingkat Pengetahuan Ibu tentang ISPA terhadap Kemampuan Merawat Balita ISPA - Enjeliika, Putri Ayu; Mahardika, I Made Rai; Sutresni , Ni Luh; Artawan, I Kadek (STIKes Hamzar, 2025)
Acute Respiratory Infection (ARI) is an infection caused by microorganisms in respiratory tract structures that do not function for gasexchange, including the nasal cavity, pharynx and larynx. This research aims to determine the relationship between the mother's levelof knowledge about ISPA and the mother's ability to care for ISPA toddlers.This research design uses quantitative descriptive with a cross-sectional approach. The sample consisted of 94 mothers with ISPA toddlers who were selected using Random Sampling techniques based on inclusion criteria. The data collection tool uses a questionnaire. The research uses the Chi-Square test. Theresults of the research can be concluded that there is a significant relationship between the level of knowledge and the ability to carefor ISPA toddlers at theKuta II Community Health Center in 2024 with a p value of 0.006.Based on the research results above, the level of knowledge of mothers and how to care for toddlers with ISP can be increased by providing education to patient parent respondents in order to reduce the incidence of ISP at the Kuta II Community Health Center in 2024.